Pagtanggap sa Intralingguwal na Pagsasalin ng Pasyong Bikol ni Tranquilino Hernandez (Reception of the Intralingual Translation of Tranquilino Hernandez’s Pasyong Bikol) - Sahagun, Rizalyn; Victoria, Vasil (Social Sciences and Development Review, 2024)
The power of translation is evident because it intellectualizes the language and the person itself in its long process especially in the current context. A proof of this reality is the change in orthography used in religious and cultural texts such as Pasyong Bikol. This study focused on the intralingual translation of the Bikol Passion, identified the Bikol and Filipino Orthography rules highlighted by intralingual translation. This study is subjected to Descriptive-qualitative design. Study participants were selected using Convenience Sampling and Purposive Sampling from Dominorog Calabanga and Naga City, Camarines Sur. Focus Group Discussion (FGD) and interviews were also used here. It was discovered in this study that from the familiarity and perception of the words or symbols used in the modern version of Passion, all the participants positively recommend and accept the Intralingual translation. In general, it is suggested that it be used in reading and studying the literature, culture, and even history of Bikol Passion. Additionally, as a religious text, the content of the modern version has not been changed. This was seen as a preliminary study to promote the intralingual translation of other religious works in Bikol.
Keywords: Pasyong Bikol; Ortograpiyang Bikol; Ortograpiyang Pambansa; Kritisismong Pampagsasalin; Intralingual Translation